2007
DOI: 10.1038/sj.ejhg.5201901
|View full text |Cite
|
Sign up to set email alerts
|

Role of ethnicity on the association of MAPT H1 haplotypes and subhaplotypes in Parkinson's disease

Abstract: An association of the H1 haplotype and subhaplotypes in the microtubule-associated protein Tau (MAPT) gene with Parkinson's disease (PD) has been reported. To further evaluate their role in PD, we genotyped a sample set of 765 cases and controls consisting of two large European subgroups of German (n ¼ 418) and Serbian (n ¼ 347) origin for the MAPT haplotypes H1 and H2. The H1/H1 carriers were tested for three additional MAPT polymorphisms. In the Serbian sample, there was significant evidence (P ¼ 0.0108) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 26 publications
1
23
1
2
Order By: Relevance
“…The frequency of rs242562 GG genotype is higher in controls compared to that in cases, indicating it may play a protective role. These data are different from a previous study which showed that MAPT polymorphism rs242562 revealed no significant difference between PD patients and controls in Germany, Serbia and Greece [6,18,19]. The sample size, ethnic groups and environment may contribute to the different results.…”
Section: Discussioncontrasting
confidence: 99%
“…The frequency of rs242562 GG genotype is higher in controls compared to that in cases, indicating it may play a protective role. These data are different from a previous study which showed that MAPT polymorphism rs242562 revealed no significant difference between PD patients and controls in Germany, Serbia and Greece [6,18,19]. The sample size, ethnic groups and environment may contribute to the different results.…”
Section: Discussioncontrasting
confidence: 99%
“…In the population with European ancestry, the H2 haplotype has a 20% prevalence whereas it is nearly absent in East Asians [17]. Even among European populations, MAPT ethnic variations were found [16]. While there was a significant association of the H1/H1 genotype and PD in the Serbian population, the same study failed to find such association in a German population.…”
Section: Discussionmentioning
confidence: 86%
“…For example, it is known that there are ethnic variations in MAPT . Caucasians display two distinctive haplotypes; H1 and H2, a 900-kb inversion polymorphism on chromosome 17 that contains several genes including MAPT [16]. In the population with European ancestry, the H2 haplotype has a 20% prevalence whereas it is nearly absent in East Asians [17].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to different (European) environmental factors means differences in epigenetic effects on gene expression (Spielman et al, 2007). For instance, a recent study (Winkler et al, 2007) indicated H1/H1 genotype as an ethnically dependent risk factor of Parkinson's disease, and another one raised remarkable suggestions on this field . An early work also observed association regarding tau variants and Asian versus Caucasian populations in progressive supranuclear palsy (Conrad et al, 1998).…”
Section: Discussionmentioning
confidence: 99%